High-risk pregnancy: fibroids and their impact on maternal and foetal health-insights from a prospective study - Singh, Deepa; Masand, Deepa L.; Gupta, Bhumika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Uterine fibroids are common benign tumors affecting women of reproductive age, with significant implications during pregnancy. This study aimed to evaluate the maternal and fetal outcomes in pregnancies complicated by uterine fibroids. Methods: A prospective observational study was conducted on 38 pregnant women with fibroids >2 cm diagnosed by ultrasonography. Patients were followed throughout pregnancy and postpartum period. Maternal characteristics, fibroid features, pregnancy complications, and fetal outcomes were analyzed. Results: The mean age was 32.4 years, with 60.5% being primigravida. Intramural fibroids were most common (65.8%), followed by subserosal (28.9%) and submucosal (15.7%) including some patients with multiple fibroids. Common complications included preterm labor (26.3%), spontaneous abortion (15.8%), placental abnormalities (13.2%), and postpartum hemorrhage (21.1%). Caesarean section rate was 55.3%. Adverse fetal outcomes included small for gestational age (31.6%), preterm birth (26.3%), and NICU admission (23.7%). Conclusions: Pregnancy with fibroids carries significant risks for both mother and fetus. Close antenatal surveillance and appropriate management strategies are essential for optimizing outcomes.